Training pouched rats to find people. Issue 1 (2nd December 2014) - La Londe, Kate B.; Mahoney, Amanda; Edwards, Timothy L.; Cox, Christophe; Weetjens, Bart; Durgin, Amy; Poling, Alan
<x xml:space="preserve">Abstract</x> Giant African pouched rats equipped with video cameras may be a tenable option for locating living humans trapped under debris from collapsed structures. In the present study, 5 pouched rats were trained to contact human targets in a simulated collapsed building and to return to the release point after hearing a signal to do so. During test sessions, each rat located human targets more often than it located similar‐sized inanimate targets on which it had not previously been trained and spent more time within 1 m of the human target than within 1 m of the other targets. Overall, the rats found humans, plastic bags containing clothes, and plastic bags without clothes on 83%, 37%, and 11% of trials, respectively. These findings suggest that using pouched rats to search for survivors in collapsed structures merits further attention.